Hyperfunctional Neutrophils in Aged Mice Are Linked to Enhanced Bone Loss in Ligature-Induced Periodontitis - Antoine Magne; Chunxiang Sun; Sina Zargaran; Jeffrey W. Chadwick; Abdelahhad Barbour; Michael Glogauer (Dentistry Journal, 2025)
Background/Objectives: Aging alters neutrophil functions, which may contribute to the progression and severity of periodontitis-related alveolar bone loss. Neutrophils play a key role in immune defense. However, the effects of aging on neutrophil functions and their contribution to periodontal disease remain unclear. This study examined age-related neutrophil dysfunction and its impact on periodontal bone loss. Methods: We used young (6 weeks old) and aged (18 months old) C57BL/6 mice to assess age-related neutrophil function. Neutrophil migration, superoxide production, phagocytic activity, and NETosis were evaluated. A peritonitis model and a ligature-induced periodontitis model were employed to investigate the relationship between neutrophil activity and alveolar bone loss. Results: Neutrophils from aged mice exhibited reduced migration toward pathogens compared to those from young mice. However, aged neutrophils showed increased superoxide production, elevated phagocytic activity, and enhanced NETosis. In the periodontitis models, these age-related neutrophil alterations coincided with accelerated alveolar bone loss in aged mice. Conclusions: The findings indicate that aging is linked to dysregulated neutrophil functions, characterized by excessive oxidative stress, heightened phagocytosis, and increased NETosis. These functional changes may contribute to immune dysregulation and tissue damage, thereby promoting age-related alveolar bone loss in periodontitis.